(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article describes many pressing problems in the field of modern education, including inclusive education, social, legal and educational changes that occurred at different stages of the development of society, the main problem in the development of inclusive education is the issue of its full implementation in practice.